Reservoir Characteristics and Resource Potential Analysis of Transitional Shale Gas in Southern Sichuan Basin - Shan, Changan; Ye, Congchen; Zhang, Zhao; Zou, Chen; He, Fangyu; Zhang, Hanbing; Mei, Jue; Yin, Kaigui; Shi, Yakun; Li, Boshuo; Zhang, Fengqi; Diao, Yifan (Frontiers in Earth Science, 2022)
Natural gas is a clean and efficient energy source. Shale gas, one of the unconventional natural gases, is becoming an indispensable part of natural gas. Compared with marine facies shale gas, which has large-scale exploitation, marine and continental transitional facies shale gas have greater development potential. It could be the new direction of development in the future. In this article, the basic geological characteristics, sedimentary environment, and reservoir characteristics of organic-rich transitional facies shale in the southern Sichuan basin are analyzed by lithologic characteristics, chemical element analysis, reservoir space, gas bearing characteristics, and so on and are compared with domestic and abroad transitional shale gas. The results show that the sedimentary period of transitional shale of Upper Permian Leping Formation has a high paleoproductivity level and deposition rate favorable for the accumulation of organic matter in southern Sichuan basin. It was warm and humid paleoclimatic by Sr, V, Cr, Ni, Co, and other trace elements analysis. According to the experimental test analysis of reservoir characteristics, the organic matter is mainly type Ⅲ kerogen, and the thermal evolution degree is mainly overmature in the reservoir. The reservoir space is mainly of microfractures and micropores. The main types of micropore development are intergranular pore, intragranular pore, and organic pore. Compared with other shale gas regions that form industrial airflow, the study region with large thickness, highly brittle mineral content, high level of organic carbon content, and excellent gas-bearing characteristics, it has favorable conditions for shale gas accumulation. The southern Sichuan basin could be the key area for breakthroughs in the exploration and development of transitional shale gas in the next step.